Assessment Instruments of Learning Motivation and Science Learning Outcomes of Class V Elementary School Students - Ahmad Walid; Hadiwinarto Hadiwinarto (ISEJ : Indonesian Science Education Journal, 2021)
This research aims to evolve an instrument of learning motivation assessment and natural science learning outcomes. The development model used in this research was 4D, consists of define, design, develop, and disseminate. This study was only carried out until the develop stage. The subject of this research was a science learning evaluation instrument consisting of a grid, questionnaire sheet and a test of natural science learning outcome. Data collected using questionnaire and test methods. The data would be analyzed for the validity and reliability of each instrument. The average value 0.92 and 1 obtained from the results of the learning motivation assessment and learning outcome instrument validity analysis, which means that both of these assessment instruments have a very high validity. While the results of the learning motivation assessment instruments reliability analysis 0.86 and natural science learning outcome 0.87, which means that both of these instruments have a high level of reliability. From these results, it could be explained that the development of learning motivation assessment and natural science learning outcome instrument were feasible to be developed and used to make assessment of student.